Exploring athletes’ experiences and perspectives on an educational program for athletes in the Pacific Islands - Hong, Hee Jung; Kim, Sungkyung; Minikin, Brian (Frontiers in Sports and Active Living, 2025)
This exploratory study aims to understand athletes’ experiences and perceptions of the “Voices of Athletes” (VOA), an athlete support program specifically designed and implemented in the Pacific Islands. Utilizing a mixed-methods approach, combining questionnaires and short interviews, data were gathered from 414 athletes (questionnaires) and 104 athletes (interviews) during the 2019 Pacific Games in Samoa. While a Chi-square test was used for quantitative analysis to assess the association between familiarity with the VOA and interest in learning more about the program, content and thematic analyses were employed to qualitatively examine participants’ perceptions and attitudes towards the VOA. The Chi-square result indicated that although the majority of athletes were initially unfamiliar with the VOA, there was a significant association between familiarity and interest in learning more about the VOA. Accompanied by the results from the quantitative data analysis, the results of the content and thematic analysis demonstrate that athletes who participated in the VOA onsite reported positive experiences and acknowledged the program's benefits in terms of personal growth and development. Participants emphasized the educational and informative aspects of the VOA, highlighting its role in increasing athletes’ awareness of contemporary social issues, empowering them to make informed decisions, and nurturing leadership skills within their communities. The results also highlighted the potential for integrating VOA into school curricula and using it as a model for support initiatives in other countries. Expanding the program could promote personal development, responsible decision-making, and leadership among a wider young population. Overall, the VOA offers significant benefits and has strong potential for broader application and customization across diverse environments. This can significantly contribute to the comprehensive growth of athletes and young people worldwide.